Referrals from community optometrists in England and their replies: A mixed methods study. (2nd February 2022) - Harvey, Krystynne; Edgar, David F; Agarwal, Rishi; Benwell, Martin J; Evans, Bruce JW
Abstract: Purpose: Community optometrists, through routine eye examinations, identify patients with disease or ocular abnormalities requiring referral to the Hospital Eye Service. In many cases no reply to the referral letter is received, resulting in some patients being re‐referred unnecessarily, potentially increasing the number of other patients who lose sight whilst on hospital waiting lists. This study investigated, qualitatively and quantitatively, factors influencing optometric referrals and replies. Methods: The three‐phase, sequential mixed methods study started with a literature review and qualitative phase, interviewing stakeholders to identify issues for exploration in subsequent phases. The second, quantitative phase, undertook documentary analysis of 349 patient referral records from three optometric practice modalities (domiciliary, independently owned, and corporate chain) in England. A final qualitative phase obtained views from stakeholders to explore unexplained findings from the first two phases. Results: Phase 1 identified communication, financial, professional and technological issues for further exploration. In Phase 2, the referral rate was 22.2% for domiciliary provider, 2.1% for independent practice and 2.5% for the corporate chain, with the variation most likely explained by patient age and associated ophthalmic disease, illness and disability. The referral reply rate was 5.7% for domiciliary provider, 25.0% for independent practice and 4.9% for the corporate chain. The community optometrist remained unaware of the outcome of their referral in 72.8% of cases. Qualitative analyses indicate the main factors influencing referral reply rates are technology, the General Medical Practitioner, community optometrists' utility to and utility of the National Health Service and patient mobilisation. Conclusions: The low referral reply rate creates a break in the feedback loop required to raise the standard of referrals and avoid unnecessary re‐referral. Of the factors identified that influence referral reply rates, technology is key in view of the increasing use of online referral platforms. Feedback to the referring optometrist should be embedded in such systems.